Evaluating Blockchain Adoption in Indonesia's Supply Chain Management Sector - Satrya Fajri Pratama; Priyo Agung Prastyo (Bright Institute, 2024)
This research evaluated the adoption of blockchain technology in the supply chain management sector, focusing on the factors that influence the intention to use blockchain, including perceived usefulness, security, facilitating conditions, cost, regulatory support, and trust. Data were collected through a cross-sectional survey distributed to 315 individuals actively involved in supply chain management, of which 309 valid responses were obtained after a validation process that included screening questions such as prior use of blockchain technology. The study employed structural equation modeling (SEM) for data analysis. The findings highlighted that trust played a significant mediating role between perceived usefulness, security, and intention to use blockchain technology. Perceived usefulness and security were found to significantly enhance trust, which in turn positively influenced the intention to adopt blockchain. Regulatory support also had a strong positive impact on adoption intentions, underscoring the importance of clear and supportive regulatory frameworks. Cost was identified as a barrier to adoption, reflecting the need for organizations to address financial concerns associated with blockchain implementation. The results contributed to the theoretical understanding of blockchain adoption by integrating trust as a key mediator in the Technology Acceptance Model and offered practical implications for supply chain management professionals and policymakers.